Upregulation of RND3 Affects Trophoblast Proliferation, Apoptosis, and Migration at the Maternal-Fetal Interface - Ma, Xiao-Ling; Li, Xiao; Tian, Fu-Ju; Zeng, Wei-Hong; Zhang, Jun; Mo, Hui-Qin; Qin, Shi; Sun, Li-Qun; Zhang, Yu-Chen; Zhang, Yan; Lin, Yi (Frontiers in Cell and Developmental Biology, 2020)
Trophoblasts as the particular cells of the placenta play an important role in implantation and formation of the maternal-fetal interface. RND3 (also known as RhoE) is a unique member of the Rnd subfamily of small GTP-binding proteins. However, its function in cytotrophoblasts (CTBs) at the maternal-fetal interface is poorly understood. In the present study, we found that RND3 expression was significantly increased in trophoblasts from the villous tissues of patients with recurrent miscarriage (RM). RND3 inhibited proliferation and migration and promoted apoptosis in HTR-8/SVneo cells. Using dual-luciferase reporter and chromatin immunoprecipitation assays, we found that forkhead box D3 (FOXD3) is a key transcription factor that binds to the RND3 core promoter region and regulates RND3 expression. Here, the level of FOXD3 was upregulated in the first-trimester CTBs of patients with RM, which in turn mediated RND3 function, including inhibition of cell proliferation and migration and promotion of apoptosis. Further, we found that RND3 regulates trophoblast migration and proliferation via the RhoA-ROCK1 signaling pathway and inhibits apoptosis via ERK1/2 signaling. Taken together, our findings suggest that RND3 and FOXD3 may be involved in pathogenesis of RM and may serve as potential therapeutic targets.